Granulomatous Lesion in Inserted Gum-Metastasis of Renal Clear Cell Carcinoma. Case Presentation - Villanueva Sánchez, Francisco Germán (2019)
Worldwide, renal carcinoma constitutes 3% of all forms of cancer in the human body. Its biological behavior is variable depending on the biology of each individual; it tends to metastasize to contiguous sites such as adrenal glands, liver, lung, bone, lymph nodes, however, remote presentation in the oral cavity is less frequent, even in inserted gums. Granulomatous lesions of the periodontium include pyogenic granulomas, giant cell granulomas among others. The main objective of this clinical case is to describe the clinical and histopathological characteristics of oral cavity metastases as granulomatous lesions. The case of a 60-year-old female patient with a history of renal cell papillary carcinoma in the right kidney treated by nephrectomy in 2017 is presented, in 2019 she presented metastases to the left lung and oral cavity. It is currently under treatment protocol for renal clear cell metastases.